Growth of silicon based germanium tin alloys - Kasper, E.; Werner, J.; Oehme, Michael; Escoubas, Stephanie; Burle, Nelly; Schulze, J. (Thin Solid Films, 2012)
Germanium tin (GeSn) is under equilibrium a two phase (Ge + Sn) system. Single phase GeSn alloys are important for silicon based heterostructure devices as stressors for Ge channels and as candidates for direct/indirect band cross-over. Such alloys would allow superior Ge channel metal oxide semiconductor devices and optoelectronic infrared circuits on a Si substrate. Preparation of GeSn layers is possible at low growth temperatures. We discuss the challenges caused by the non-equilibrium growth and the limitations of low temperature epitaxy. Main challenges and limitations are the surface segregation, precipitations and defect accumulation in low temperature epitaxy. The problem of high lattice mismatch between Si and GeSn (> 4%) can be solved using virtual substrates with strain relaxed Ge buffer layers. The lattice mismatch can be reduced to 1% and below. Growth of pseudomorphic GeSn layers on Ge buffers/Si substrate was investigated. The samples were characterized by X-ray methods and Raman spectroscopy. High device process stability was achieved up to 600°C annealing and documented by Raman spectroscopy. Fabrication of a detector test device demonstrated feasibility for optoelectronic applications with extended infrared range. © 2011 Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Epitaxy; Germanium tin; GeSn